SHS Processing and Consolidation of Ta–Ti–C, Ta–Zr–C, and Ta–Hf–C Carbides for Ultra‐High‐Temperatures Application. Issue 8 (3rd April 2018) - Kurbatkina, Viktoria V.; Patsera, Evgeny I.; Levashov, Evgeny A.; Vorotilo, Stepan
Abstract : This review addresses the structure and phase formation mechanisms of self‐propagating high‐temperature synthesis (SHS) of single‐phase complex carbides Ta–Ti/Zr/Hf–C, as well as the consolidation of synthesized carbides by various sintering methods. Properties of the synthesized and consolidated complex carbides are described, and unique advantages of SHS method for the synthesis of ultra‐high temperature complex single‐phase carbides are highlighted. Abstract : This review addresses the structure and phase formation mechanisms during the SHS of single‐phase complex carbides Ta–Ti/Zr/Hf–C, as well as the sintering methods applied for consolidation of synthesized carbides and properties of bulk carbides specimens produced thereby. As the figure shows, SHS is a fast, simple, and facile method of synthesis of ultra‐high temperature complex single‐phase carbides and is well‐suited for the large‐scale production.